Circulating miR-206, miR-181b, and miR-21 as promising biomarkers in hypothyroidism and their relationship to related hyperlipidemia and hepatic steatosis - Mohammed, Asmaa; Shaker, Olfat G.; Khalil, Mahmoud A. F.; Abu-El-Azayem, Abeer K.; Samy, Amira; Fathy, Shaimaa A.; AbdElguaad, Mohamed M. K.; Mahmoud, Fatma A. M.; Erfan, Randa (Frontiers in Molecular Biosciences, 2024)
Background: Thyroid hormones (THs) signaling has profound effects on many physiological processes. THs regulate the expression of certain miRNAs and their target messenger RNAs (mRNAs) in various tissues and cells. Aim: This research aimed to investigate miR-181b, miR-206, and miR-21 in the serum of patients with subclinical and overt hypothyroidism to determine their possible role in the diagnosis of the disease and their relationship to clinical disorders related to hypothyroidism. Methods: This study included ninety participants, divided evenly into three groups as follows: patients with overt hypothyroidism diagnosed clinically, radiologically, and by investigation (30), subclinical hypothyroid patients (30), and healthy volunteers (30). The patients had a thorough medical history and underwent a clinical examination. Laboratory tests included plasma cholesterol, LDL, HDL, TGs, liver and renal function tests, CBC, fasting insulin, HOMA-IR, HbA1c, TSH, and free T4. The serum levels of miR-21, miR-206, and miR-181b were measured using qRT-PCR. Results: miR-206 and miR-181b levels were higher in the subclinical group, followed by the hypothyroid and control groups. For miR-21, there was a significantly lower mean value in both the hypothyroid and subclinical groups than in the control group, with no difference between the two groups. Both miR-206 and miR-181b showed a significant negative association with albumin and free T4 levels and a significant direct association with GGT, ALT, AST, creatinine, uric acid, TGs, TC, LDL, TSH, thyroid volume, and CAP score. The same correlation pattern was observed for miR-181b, except that it was not significantly correlated with the TGs. For miR-21 levels, there was a significant positive correlation with albumin, free T4 level, and kPa score and a negative correlation with GGT, ALT, AST, creatinine, uric acid, HOMA-IR, HbA1c, TC, LDL, TSH, and CAP score. Cases with F1 kPa score and S2 CAP scores had significantly higher averages for miR-206 and miR-181b, with a p-value of 0.05. Moreover, miR-21 levels were significantly lower in the S2 CAP score group. Conclusion: These miRNAs (miR-206, miR-181b, and miR-21) may be used as diagnostic biomarkers for hypothyroidism. They may be used as therapeutic targets to control dyslipidemia and hepatic steatosis during hypothyroid disease.